Surgical palliation for malignant disease requiring locoregional control - Blakely, Andrew M.; McPhillips, Jane; Miner, Thomas J (Annals of Palliative Medicine; Vol 4, No 2 (April 30, 2015): Annals of Palliative Medicine, 2015)
Background: Surgical palliation of cancer is best defined as procedures performed with non-curative intent to improve quality of life or control symptoms of advanced malignancy. Soft tissue involvement of advanced malignancies may produce symptoms such as pain, bleeding, or odor that significantly reduce quality of life. Literature on outcomes of palliative resection of soft tissue malignancy for local or regional control is lacking. Methods: Soft tissue resections performed with palliative intent for locoregional control were identified from a prospectively maintained palliative surgery database at a tertiary care center from January 2004 to July 2013. Tumor type, presenting symptom, procedure performed, and symptom recurrence were recorded. Patients were followed for at least 60 days or until death. Results: Thirty-one patients who underwent palliative soft tissue resection for local control were identified. Primary tumor types included melanoma (n=9, 29.0%), squamous cell carcinoma (n=9, 29.0%), sarcoma (n=5, 16.1%), breast (n=3, 9.7%), and other (n=5, 16.1%). Eighteen of 31 patients (58.1%) underwent resection for pain, two (6.5%) for bleeding, and eleven (35.5%) for local control or other symptoms. Procedures were performed on the trunk (n=17, 54.8%), extremities (n=7, 22.6%), head/neck (n=5, 16.1%), or multiple areas (n=2, 6.5%). Eleven of 31 patients (35.5%) underwent axillary, inguinal, or neck lymph node dissection, seventeen (54.8%) radical resection, and three (9.7%) wound excision. Split-thickness skin graft was performed in 6 of 17 radical resections (35.3%). Five patients (16.1%) had symptom recurrence at the site of the initial palliative procedure, of whom four (12.9%) underwent a second palliative procedure. Seven patients (22.6%) had new disease-related symptoms develop during follow-up. Thirty-day morbidity was 29.0%; mortality was 3.2%, which was associated with progression of disease. Conclusions: Palliative surgery for local control of advanced soft tissue malignancy can provide durable symptom relief and improved quality of life. These procedures positively impact patients regardless of primary tumor type or tumor extent. Careful patient selection is important in order to maximize benefit of surgical palliation and minimize morbidity and mortality.